Penolakan Masyarakat Terhadap Verifikasi Penetapan Arah Kiblat Oleh Badan Hisab Rukyat Kemenag Kota Pekalongan di Pekalongan - Miskiyah, Miskiyah (Al-Hukkam: Journal of Islamic Family Law, 2021)
Qibla is one of the conditions for the validity of prayer, but in fact the problem of Qibla direction is a problem for Muslims. In the City of Pekalongan, the problem of the Qibla of mosques/mushola is still a lot less accurate and inappropriate, but when the mosque/mushola was re-measured and the results were not in accordance with the Qibla they used to be, they did not receive the results of the leverage from the BHRD of the Ministry of Religion of Pekalongan City, instead they preferred the previous Qibla direction because they believe more in their ancestors. This paper examines how the attitude of the BHRD of the Ministry of Religion of Pekalongan City in responding to the community regarding the lever of Qibla direction by the BHRD of the Ministry of Religion and why the people of Pekalongan City refuse to verify the Qibla direction carried out by the BHRD of the Ministry of Religion of Pekalongan City. The theory used in determining the Qibla direction of the Ministry of Religion of Pekalongan City BHRD using the basis of the Qur'an, Al Hadith, with the trigonal ball formula and how the steps for determining the Qibla direction are, but in reality this theory does not apply to people who reject the lever of direction. The direction of the Ministry of Religion of Pekalongan City for several reasons and it turns out that theory and practice are not the same.